Multi-Criteria Comparative Analysis of Proactive Safety Strategy of An Organization Exemplified by Polish Companies - Tomasz EWERTOWSKI; Sebastian KUBASIŃSKI (Communications of International Proceedings, 2021)
The safety condition in the organization is determined by many factors and indicators whose the analysis and assessment may be undergone to a larger or minor extent. Depending on possessing various kinds of data and a general attitude to solving problems within the scope of safety three strategies of safety management are distinguished: reactive, proactive and predictive. In a modern organization following by a proactive strategy plays a crucial role in providing the safety. The research was carried on and based on the data obtained from the four companies. The survey was based on the questionnaire consisting of 8 questions to measure the proactive strategy of the organizations. Firstly, authors present definitions of terms which are connected with proactive attitude and strategy in the organization. Finally, findings of properly conducted research and its implications have been presented. The results of the analyses allowing managers to find out what aspects need to be taken into account to increase the proactive strategy of the organization.
Keywords: Safety Management Systems; Proactive Safety Strategy; Incidents; Occupational Health and Safety.